Analisis Pemikiran Pendidikan Kritis Perspektif Ibnu Thufail - Labib Ulinnuha; Tejo Waskito; Yulita Putri (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2024)
This study aims to find the construction of critical education contained in the novel